DINAMIKA PESANTREN DALAM PERSPEKTIF EKONOMI - Mursyid Mursyid (Millah: Journal of Religious Studies, 2011)
This paper discusses the strategic role of boarding schools that have been marginalized in the national education system and global challenges towards economic independence. In today's era of globalization need to reform schools curriculum to adapt to the progress of free market economics and Islamic economics to economic independence will be achieved. Hence, economic institutions at the seminary need to be empowered.